Professional pressure on teachers and the educational process - Soufi, Naima (Journal of Human Sciences, 2021)
The teaching profession is one of the most pressing professions because of the responsibilities and duties that it imposes on the teacher, which cause him the burden, the weight and the tension resulting from poor working conditions, so we will try in this chapter to tackle the subject of professional pressure in the field of education and then to highlight the most important theoretical models that explain the pressures of work And the sources of professional stress in general, focusing on the sources of professional pressure among teachers.